FAKTOR KEBERHASILAN ATLET ATLETIK LARI PADA ANAK DENGAN GANGGUANSPEKTRUM AUTIS D KOTA BANDUNG - Isma Rizqi Ramadhan, - (2020)
Excellence can be achieved by anyone who has a certain skill in the field, including disability. Many disability athletes have certain achievements, one of whom D child with autism spectrum disorder. D has a lot of athletic performance. In achieving its success, certainly D has factors to support its success, whether within him or outside. The study was intended to get an idea of a success factors in an athlete who was a child with autism spectrum disorder. The approach is qualitative using case study methods, and using data collection techniques interviews, observations, and documentary studies. The results of this study indicate that there is an aspect to support each factor. In physical factors, D had the ideal posture. Then the factors runing technique, D could be in stand or squat, balanced hand and foot movement coordination and reach a finish, while the motivating factors show enthusiasm and willingness to participate in the exercise from the d through to the finish. Supporting factors include aspects of coaches, parents, sports organizations, infrastructure facilities, and schools. Those aspects have their respective support in developing potential D.